Implementation of clinical pharmacy in Turkey - (:unkn) unknown (My University, 1998)
A program leading to degree of master of science in clinical pharmacy is discussed which is designed to prepare specialists having the basic concepts of clinical pharmacy and skills to conduct researches in drug evaluation. The program is composed of a didactic session, clerkship and research work (thesis). The didactic session includes courses of biology of diseases, infectious diseases, advanced biopharmaceutics and clinical pharmacokinetics, clinical biochemistry, drug information, drug monitoring, applied therapeutics, immunology, biostatistics and pharmacy practice. Clerkships include the following areas: inpatient pharmacy, community pharmacy, internal medicine, pediatrics and surgery. Weekly 3 hours discussion session at college or clerkship site are scheduled to review these experiments. This program helps to be developed leaders in clinical pharmacy in Turkey and promotes the development of a clinically oriented attitude in students and staff members in the college as well as assists in the stepwise transition from a pharmacy school with primary emphasis on dispensing to a more clinically (patient) oriented pharmacy program. In this article a suggested B. S. program for faculty of pharmacy in Turkey and a need for continuing education courses concerning the new roles of pharmaceutists (clinical pharmacy) were also discussed.
Keywords: Clinical pharmacy service; Education, pharmacy; Education, pharmacy, continuing; Education, pharmacy, graduate; Pharmacy; Turkey